2019
DOI: 10.1038/s41598-019-38649-w
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody-based indirect competitive enzyme-linked immunosorbent assay for flubendiamide detection

Abstract: Flubendiamide (FD), the first commercial phthalic acid diamide that targets insect ryanodine receptor (RyRs), has played an important role in pest management. With its extensive worldwide application, a rapid and convenient method to detect its existence in the environment is necessary. In this study, an indirect competitive enzyme-linked immunosorbent assay (icELISA) was developed to analyse FD residue on environmental and food samples. The established icELISA showed a half maximal inhibition concentration (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Figure C displays the corresponding fitted curves. In a study conducted by Li et al, changes in ionic strength were shown to have a minimal effect on the sensitivity of the ic-ELISA. However, as mentioned in a published report by Reverberi, R. and Reverberi, L., the ion concentration can potentially interfere with the binding of charged groups to antigenic epitopes or antibody binding sites, thereby impeding the interaction between the antigen and antibody.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure C displays the corresponding fitted curves. In a study conducted by Li et al, changes in ionic strength were shown to have a minimal effect on the sensitivity of the ic-ELISA. However, as mentioned in a published report by Reverberi, R. and Reverberi, L., the ion concentration can potentially interfere with the binding of charged groups to antigenic epitopes or antibody binding sites, thereby impeding the interaction between the antigen and antibody.…”
Section: Resultsmentioning
confidence: 95%
“…Based on the acetonitrile-optimized standard curve in Section 3.1.4, the ic-ELISA has a minimum detection limit of 1.7 ng/ mL and a linear range of 1.7−73.2 ng/mL in various agricultural samples, thereby meeting the detection limit requirements for the aforementioned samples. Li et al 28 and Yin et al 32 both utilized nitrogen gas drying in the sample preparation and extraction process. Similarly, to address matrix effects, the prepared sample solutions were diluted with PBSTG buffer at a 10-fold dilution followed by ic-ELISA detection.…”
Section: Establishment Of the Standard Curve For Prometryn Colloidal ...mentioning
confidence: 99%
“…-phthalamide (A1 ) were prepared as described previously. 12 Preparation of the RyR P. americana adults were purchased from the Tianyu Medicinal Insects Breeding Base (Bozhou, China), and RyR membranes were extracted from their leg muscles using the procedure developed by Schmitt et al, 13 with minor modifications. All steps were performed on ice, and two buffers were used: (A) 50 mM Tris-HCl, pH 7.4, containing 1 μg/mL each of aprotinin, pepstatin, and leupeptin; and (B) 1.5 M KCl, 300 mM sucrose, 0.5 mM CaCl 2 , 20 mM Tris-HCl, pH 8.0, containing 1 μg/mL each of aprotinin, pepstatin, and leupeptin.…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization (WHO) has conditionally approved a batch of SARS-CoV-2 antigen reagents for clinical application ( Ye et al, 2022c ). However, the currently established SARS-CoV-2 antigen assays, such as lateral flow immunochromatographic assay (LFIA) and enzyme-linked immunosorbent assay (ELISA), have inevitable shortcomings such as inadequate sensitivity (poor for viral concentrations less than 0.1 ng/mL), long detection time, and low repeatability ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%